Metaphors in Mata Najwa Podcast Episode: “Eklusif, Ganjar Pranowo dan Piala Dunia” | Mata Najwa - mawaddah, suci (Fakultas Ilmu Budaya, Universitas Mulawarman, 2023)
This research discusses the use of metaphor features in the Podcast Najwa Shihab Episode “Eklusif: Ganjar Pranowo dan Piala Dunia” | Mata Najwa. This podcast is one of the contents of Najwa Sihab's Youtube channel which is the source of data in this study. The purpose of the research is to analyze the characteristics of metaphors used and their relationship with power. This research was conducted using Fairclough's (1992) critical discourse research approach, which views language as a means of power. The research method used was descriptive qualitative. Through this research, the author found six metaphorical expressions from the podcast episode